Enhancing nosiheptide production in Streptomyces actuosus by heterologous expression of haemoprotein from Sinorhizobium meliloti. (June 2016) - Mo, Q.; Zhang, H.; Liu, Q.; Tang, X.; Zhao, L.; Zan, X.; Song, Y.
Abstract: Oxygen deficiency is a critical limiting factor for nosiheptide production in Streptomyces actuosus during fermentation. To alleviate oxygen limitation and enhance the yield of nosiheptide, haemoprotein from Sinorhizobium meliloti (SmHb) was overexpressed in S. actuosus with overexpression of haemoglobin from Vitreoscilla (VHb) as a positive control. The expression of SmHb and VHb in S. actuosus was confirmed by SDS‐PAGE and CO‐difference spectra analysis. The results showed that S. actuosus recombinant strain with SmHb expression had higher nosiheptide production (increased by 151%) than the wild strain (WT) under the low aeration conditions, which was similar with S. actuosus mutant strain with VHb expression. Furthermore, two copies of SmfHb gene were integrated in S. actuosus, which further increased the nosiheptide production by approx. 1·9‐fold compared with original strain, and final nosiheptide yield was up to 2352 μ g ml −1 . These results suggested that engineering of SmHb expression could be used as an efficient method for constructing a high nosiheptide‐accumulating strain. Significance and Impact of the Study: The significant improvement of nosiheptide production was found in recombinant strain with overexpressed sm gene. And further improvement was obtained in the two copies of sm overexpressing strain. These results suggested that engineering of SmHb expression could be used as an efficient method for constructing a high nosiheptide‐accumulating strain. Abstract : Significance and Impact of the Study: The significant improvement of nosiheptide production was found in recombinant strain with overexpressed sm gene. And further improvement was obtained in the two copies of sm overexpressing strain. These results suggested that engineering of SmHb expression could be used as an efficient method for constructing a high nosiheptide‐accumulating strain.